Potencial antimicrobiano dos extratos de própolis (Verde, Vermelha e Marrom) - Oliveira, Laís Aryel Andrade de (Universidade Federal Rural do Semi-Árido, 2019)
Propolis, produced by bees has several functions in the hive, among them defensive action against invaders and insects, as well as promoting the aseptic environment of the same. In this way, the objective was to evaluate the antibacterial potential of the propolis extracts (green, red and brown) against strains of ten selected microorganisms. The extracts of green, red and brown propolis were used in concentrations of 8%; 6%; 4% for each extract, which corresponds to 34.28 mg / ml, 25.714 mg / ml, and 17.142 mg / ml respectively. To determine the minimum inhibitory concentration (MIC) of the propolis extracts against the selected microorganisms, the microdilution test according to the CLSI (2015) was performed using 96well flat bottom plates, the minimum bactericidal concentration test CBM) in order to evaluate the effect of extracts if it would be bactericidal or bacteriostatic. The data were submitted to analysis of variance (ANOVA) and the means were compared using the Tukey test, at a level of 5% of significance using the SISVAR program version 5.6. Therefore, the red propolis extract had a 40% inhibition rate on the tested microorganisms. Where the concentration of 34.28 mg / ml (8%) of the red propolis extract was shown to be more effective against the tested microorganisms. The results showed MIC values close to those found in the literature. For extracts of green and brown propolis, both had no antimicrobial activity at the concentrations tested, and there was no statistical difference between them.
Monografia
Keywords: Potencial antimicrobiano; Própolis; Apis mellifera; Compostos fenólicos; CIENCIAS AGRARIAS::ZOOTECNIA